Advances in multiparametric magnetic resonance imaging combined with biomarkers for the diagnosis of high-grade prostate cancer - Li, Song-lin; Zha, Ming-yong; Wang, Qi; Tang, Yong (Frontiers in Surgery, 2024)
Clinical decisions based on the test results for prostate-specific antigen often result in overdiagnosis and overtreatment. Multiparametric magnetic resonance imaging (mpMRI) can be used to identify high-grade prostate cancer (HGPCa; Gleason score ≥ 3+4); however, certain limitations remain such as inter-reader variability and false negatives. The combination of mpMRI and prostate cancer (PCa) biomarkers (prostatespecific antigen density, TMPRSS2:ERG gene fusion, Michigan Prostate Score, ExoDX Prostate Intelliscore, Kallikrein 4Kscore, Select Molecular Diagnosis, Prostate Health Index, and Prostate Health Index density) demonstrates high accuracy in the diagnosis of HGPCa, ensuring that patients avoid unnecessary prostate biopsies with a low leakage rate. This manuscript describes the characteristics and diagnostic performance of each biomarker alone and in combination with mpMRI, with the intension to provide a basis for decision-making in the diagnosis and treatment of HGPCa. Additionally, we explored the applicability of the combination protocol to the Asian population.